Distinctive features of the central synaptic organization of Drosophila larval proprioceptors - Greaney, Marie R.; Wreden, Chris C.; Heckscher, Ellie S. (Frontiers in Neural Circuits, 2023)
Proprioceptive feedback is critically needed for locomotor control, but how this information is incorporated into central proprioceptive processing circuits remains poorly understood. Circuit organization emerges from the spatial distribution of synaptic connections between neurons. This distribution is difficult to discern in model systems where only a few cells can be probed simultaneously. Therefore, we turned to a relatively simple and accessible nervous system to ask: how are proprioceptors' input and output synapses organized in space, and what principles underlie this organization? Drosophila larvae have six left-right pairs of proprioceptors in each segment. Using the larval connectome, we generated a map of the input and output synapses of 34 proprioceptors in several adjacent body segments. We found three distinguishing features of proprioceptor synapses: (1) Generally, individual proprioceptor types display segmental somatotopy. (2) Proprioceptor output synapses both converge and diverge in space; they are organized into six spatial domains, each containing a unique set of one or more proprioceptors. (3) Proprioceptors receive few inhibitory input synapses. Further, we compared the organization of proprioceptors and other somatosensory neurons, revealing that the above three properties are specific to proprioceptors. Thus, we have generated the most comprehensive map to date of how proprioceptor synapses are centrally organized. This map documents previously undescribed features of proprioceptors, raises questions about underlying developmental mechanisms, and has implications for downstream proprioceptive processing circuits.